Spatial analysis of environmental sanitation and stunting incidents - Tanjung, Risnawati; Lestrina, Dini; Sinaga, Jernita (International Journal of Public Health Science (IJPHS), 2024)
Environmental factors such as sanitation and hygiene, drinking water sources, quality of drinking water, and ownership of latrines are indirect factors causing stunting. This study aims to analyze the distribution of stunting and environmental sanitation factors that cause stunting in Dairi District, North Sumatra, Indonesia. The case-control design was carried out with 172 toddlers. The distribution pattern of stunting and the association of patient characteristics and environmental risk factors was carried out using the Geographic Information System. Data on healthy clean-living behavior was collected using a questionnaire, and microbiological laboratory tests measured water quality. The spatial analysis uses an average nearest-neighbor overlay. The association of characteristics and risk factors with the incidence of stunting was analyzed using chi-square and logistic regression. The average nearest neighbor analysis shows that the nearest neighbor index is 0.19 ( 0.05) are unrelated to stunting. The pattern of distribution of cases tended to be in clusters, and no relationship was found between population density and the incidence of stunting. The findings of this study provide a new understanding that health promotion to prevent stunting does not only focus on fulfilling nutrition but also on healthy clean-living behavior and water quality.